Investigating the role of the interleukin-23/-17A axis in rheumatoid arthritis. - Hillyer, P; Larché, M; Bowman, E; McClanahan, T; de Waal Malefyt, R; Schewitz, L; Giddins, G; Feldmann, M; Kastelein, R; Brennan, F (2009)
OBJECTIVE: IL-23 is a pro-inflammatory cytokine proposed to be central to the development of autoimmune disease. We investigated whether IL-23, together with the downstream mediator IL-17A, was present and functional in RA in humans. METHODS: RA synovial cells were cultured in the presence or absence of antibodies directed against IL-23p19 or -23R and -17. IL-23, -12, -17, and their receptors, and IL-6, -1beta and TNF-alpha were measured by ELISA and/or PCR. RESULTS: Small amounts of cell-associated IL-23 (median 110 pg/ml) were detected in RA synovial cultures, and found to be functional as IL-23R blockade resulting in a significant inhibition of TNF-alpha (57%), IL-1beta (51%) and IL-6 (30%). However, there was a considerable variability between individual patient samples, and anti-IL-23p19 was found to be considerably less effective. IL-17A protein was detected in approximately 40% of the supernatants and IL-17A blockade, in IL-17A-producing cultures, resulted in a small but significant inhibition of TNF-alpha (38%), IL-1beta (23%) and IL-6 (22%). Addition of recombinant IL-23 to cultures had a variable effect on the spontaneous production of endogenous IL-17A with enhancement observed in some but not all cultures, suggesting that either the low levels of endogenous IL-23 are sufficient to support cytokine production and/or that the relevant Th17 cells were not present. CONCLUSIONS: These results suggest that although IL-23 may have pathogenic activity in a proportion of patients with late-stage RA, it is not abundantly produced in this inflammatory tissue, nor does it have a dominant role in all patient tissues analysed.